Single-cell profiling of T cells uncovers a tissue-resident memory-like T-cell subset associated with bidirectional prognosis for B-cell acute lymphoblastic leukemia - Lai, Wenpu; Wang, Xiaofang; Liu, Lian; Xu, Ling; Mao, Lipeng; Tan, Jiaxiong; Zha, Xianfeng; Zhan, Huien; Lei, Wen; Lan, Yu; Chen, Guobing; Li, Yangqiu; et al. (Frontiers in Immunology, 2022)
The character and composition of leukemia-related T cells are closely related to the treatment response and prognosis for patients. Though B cell-acute lymphoblastic leukemia (B-ALL) patients have benefited from immune-based approaches, such as chimeric antigen receptor T cells therapy, some of them still end with poor prognosis. We analyzed the peripheral blood T cell single-cell RNA sequencing data of three B-ALL patients, using data from 11 healthy individuals as controls. Unbiased analysis enabled the discovery of circulating CD103+ T cell (CD3+CD103+MKI67+), also defined as tissue resident memory-like T (Trm-like) cell, population was elevated in B-ALL patients, which expressed high level of cell proliferation and exhaustion related genes. In addition, cell fate trajectory analysis showed these Trm-like cells, which shared TCR clonotypes with exhausted T (Tex) cells and effector T (Teff) cells, were supposed to transition into Teff cells, however, mainly transformed into Tex cells in leukemia environment. More importantly, Trm-like cells transformation into Teff cells and Tex cells potentially led to favorable or poor prognosis for B-ALL patients, respectively. Together, these results provided a unique insight of alteration of leukemia related T cells, also showed a potential immunotherapy direction and prognosis assessment model for B-ALL patients.